Contour optimization of suspension insulators using real coded genetic algorithm with simulated binary crossover - Gunasekaran, S.; Iruthayarajan, M. W. (2013 International Conference on Pattern Recognition, Informatics and Mobile Engineering (PRIME), 2013)
Electrical-field distribution along the insulator surface strongly depends upon the contour design, besides the effect of pollution. The insulator contour should be designed to reach a desired uniform and minimal tangential field to increase the onset voltage of surface flashover. In this paper, with the finite element method (FEM) integrated, the real coded genetic algorithm (RGA) with simulated binary crossover (SBX) approach is proposed for contour optimization of a suspension insulator. The aim of the contour optimization is to minimize the Tangential electric field and make the tangential electric field as uniform, subject to design constraints. The results show that a rather uniform and minimal tangential field distribution can be obtained through the proposed approach.